Pendidikan Nilai Pada Anak Usia Dini di Kelompok Bermain dan Taman Kanak-Kanak Islam Terpadu - Setiawati, Suzzanna; Arifin, Zainal (PROGRAM STUDI PENDIDIKAN GURU RAUDLATUL ATHFAL (PGRA) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2015)
This study is based on the phenomenon of globalization, one of which had a negative impact on the values of life. Another impact of globalization is the emancipation of women who want a career. Busyness of parents who spend a lot of time resulting in early childhood education is not running with the maximum. This study is a qualitative research took place in KB and TK IT Karima Aqila Sinduadi, Sleman, Yogyakarta. data collection by observation, in-depth interviews and documentation. The results showed: (1) the value of education held in KB and TK IT Karima Aqila are: (a) the value of religious education, (b) Education of moral values, (c) social values education. (2) The methods used include: exemplary, habituation, advice, telling stories, singing, practices, supervision, communicate to parents, a tangle of love, punishment, providing initial information to children, play.